Insights into hydraulic conductivity, mechanical properties, and microstructure of fly ash-modified clay anti-seepage layer to red mud leachate - Yibo Zhang; Yujie Ding; Yulong Wang; Yue Yu; Qian Chen; Zheng Wu (Case Studies in Construction Materials)
The environmental impact of red mud leachate, particularly from tailings ponds, has become a significant concern due to its highly alkaline nature and potential to cause widespread soil and water contamination. Addressing this issue requires effective strategies for mitigating the leakage of contaminants, such as heavy metals and hazardous alkalis, into surrounding ecosystems. This study explores the use of fly ash-modified clay liners as a solution to contain and treat red mud leachate pollutants, including heavy metals and alkalis. Macro-scale tests, such as permeation and unconfined compression tests, combined with micro-scale analyses (XRD, SEM, BET), investigate the influence of varying fly ash content on the hydraulic conductivity, mechanical properties, and microstructure of the clay liners. The findings show that fly ash significantly reduces the hydraulic conductivity of the liners, improving their effectiveness in preventing seepage. It also enhances the liners' ability to adsorb heavy metal ions and increases their mechanical strength, especially cohesion, with optimal performance at a 9 % fly ash content. The study further reveals that pozzolanic reactions in the alkaline environment of red mud lead to the formation of cementitious gel binders (C-S-H, C-A-H), which reduce pore sizes and create a denser, more impermeable structure. These improvements in both physical and chemical stability demonstrate the potential of fly ash-modified clay liners as an effective, sustainable solution for managing red mud tailings ponds. This study provides valuable support for environmental management of red mud tailings ponds and the sequestration of red mud leachate waste.